2005
DOI: 10.1007/s00428-005-0105-1
|View full text |Cite
|
Sign up to set email alerts
|

High expression of RELP (Reg IV) in neoplastic goblet cells of appendiceal mucinous cystadenoma and pseudomyxoma peritonei

Abstract: The regenerating protein (Reg)-like protein (RELP, also known as Reg IV) is a recently characterized fourth member of the human Reg protein family. The Reg proteins are small, about 20-kD-sized, secretory proteins of C-lectin type. The previously known Reg proteins have been functionally implicated in regeneration, proliferation, and differentiation of the pancreas, liver, and gastrointestinal mucosa. To study the tissue expression of RELP, we raised a monoclonal antibody to RELP. By immunohistochemistry and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…However, REGIV was clearly increased in goblets in active disease and seemed to be secreted with the mucus. The observation that REGIV is located to goblets corresponds to previous findings by Kamarainen and coworkers [16], and a recent study on appendiceal mucinous cystadenoma and pseudomyxoma peritonei [17] also found REGIV in goblets and mucus. This suggests that REGIV is secreted and may have a luminal mode of action.…”
Section: Discussionsupporting
confidence: 89%
“…However, REGIV was clearly increased in goblets in active disease and seemed to be secreted with the mucus. The observation that REGIV is located to goblets corresponds to previous findings by Kamarainen and coworkers [16], and a recent study on appendiceal mucinous cystadenoma and pseudomyxoma peritonei [17] also found REGIV in goblets and mucus. This suggests that REGIV is secreted and may have a luminal mode of action.…”
Section: Discussionsupporting
confidence: 89%
“…Three genes showed a characteristic upregulation in pCRCs and a subsequent downregulation in LMs: SPINK4 , MMP3 and REG4 . Whereas SPINK4 and REG4 are expressed in differentiated cells (goblet cells and neuroendocrine cells, respectively48 49), MMP3 is mainly expressed in the connective tissue, implicated in the turnover of extracellular matrix to allow cell migration 50. Why these three genes confer a possible tumour promoting function in primary tumours, whereas their expression seems to be dispensable in liver metastases, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Present knowledge of the mRNA expression patterns of the various REG s in human colonic mucosa is extremely limited, with only a few studies demonstrating the expression of REG1A and REG4 in colorectal cancer and pseudomyxoma peritonei of the appendix (Astrosini et al 2008; Heiskala et al 2006). In the present study, we have utilised an in situ hybridisation (ISH) method involving branched-chain DNA technology, enabling us, for the first time, to localise all human REGs in normal and inflamed colon.…”
Section: Introductionmentioning
confidence: 99%